Turmeric as a local drug delivery in periodontitis: A review of literature - Arnav Mukherji; Sinthiya Bose (Wolters Kluwer Medknow Publications, 2022)
Periodontitis is a multifactorial disease. Traditional methods like toothbrushing and manual scaling and root planing are the treatment of choice. However, these methods are time-consuming and not fully effective. To restore periodontal health systemic antibacterials are used as adjuncts, but due to side effect and inability to reach target areas, other alternative methods were devised. Various handicaps of systemic drugs such as side effects, resistance, and growth of opportunistic infection, local drug delivery agents (LDD) in periodontology have gained acceptance and popularity. Haldi/turmeric has been used in our country since time immemorial. It has vast array of therapeutic uses. This review attempts to shed light on the efficacy of curcumin as LDD agent in periodontal infections.